The practice and potential of the SITES v2 rating system for the sustainable design of a landscape: A case study of Chicago’s Navy Pier - Jin, Lin; Wang, Yilei (Frontiers in Environmental Science, 2023)
The landscape is a synthesis of cultural and natural processes in a place that can be designed and maintained to improve and regenerate the natural benefits and services of ecosystems. The Sustainable Sites Initiative has developed a rating system that identifies and advances best practices for landscape architecture. The SITES v2 Rating System was produced through a multi-year iterative process and incentives sustainable landscape practices by using an ecosystem services framework. Opportunities for continuing research on how SITES v2 encourages the creation of a landscape sustainability system and drives more sustainable land development will become apparent as it expands in application, scope, and impact. To illustrate the practice and potential of SITES v2 for sustainable landscape design, this research is primarily a literature review with the specific context of the SITES gold-certified project, Navy Pier in Chicago. The results show that SITES v2 is an important tool for transforming theory into the implementation of ecosystem services and guiding design decisions towards sustainable outcomes. It also promotes the entire project's accountability to a higher standard of best practices and results in a more sustainable site. In the context of contemporary landscape architecture practices, SITES v2 may lead to the transformation of sustainable landscape design. This study can promote the ongoing application of SITES v2 and the creation of a better sustainable landscape through design. It holds the potential to highlight how the methodology on which SITES has been created can be linked with the development of future cities and the management of urban landscapes.